The Influence of Training on Work Effectiveness - Natanael Setiahadi, Johanes; Bachtiar, M. Faris Adnan; Audreya, Qonita (PT Bangun Harapan Bangsa, 2024)
This research aims to determine the effect of training on employee performance at Khoe Pek Goan Bloemenstad. Data taken using quantitative methods and obtained from respondents who are employees of Khoe Pek Goan Bloemenstad. Employee performance is influenced by training activities with the aim of increasing human resource capacity in facing competition in business. The research results show that effective training can improve the quality of human resources so that employee performance increases.